Anatomy of the optic nerve based on cadaveric dissections and its neurosurgical approaches: a comprehensive review - R. López-Elizalde; M. Godínez-Rubí; Ya. Lemus-Rodríguez; E. Mercado-Rojas; T. Sánchez-Delgadillo; D. Sánchez-Delgadillo; A. Campero; R. G. Párraga (Сеченовский вестник)
Vision is a complex sense that is widely represented in the cortex and involves multiple pathways that can be affected by conditions amenable to surgical treatment. From a neurosurgical point of view, the treatment of major lesions affecting the optic nerve, such as tumours, intracranial hypertension, trauma and aneurysms, can be approached depending on the segment to be worked on and the surrounding structures to be manipulated. Therefore, surgical manipulation of the visual pathway requires a detailed knowledge of functional neuroanatomy. The aim of this review is to present the functional and microsurgical anatomy of the second cranial nerve, through illustrations and cadaveric dissections, to support the choice of the best surgical approach and avoid iatrogenic injuries. For this purpose, a literature search was performed using the PubMed database. Additionally, cadaveric dissections were performed on adult cadaver heads fixed with formaldehyde and injected with coloured silicone.